Potential cancer risk estimates from trihalomethanes in peri-urban settings of Kawama East of Mufulira, Zambia. (30th May 2022) - Muleya, Benson; Mwaanga, Phenny; Daka, Philip S.; Nguvulu, Alick
Abstract: In this study, we report the formation and cancer risk estimation of trihalomethanes (THMs) emanating from 'ex-situ' chlorination of shallow hand-dug well water obtained from a peri-urban area of Mufulira District, Zambia. The aim of the study was to evaluate the potential cancer risks for people in this area where chlorine water disinfection at the household level is commonly practiced. Water samples from 13 randomly selected hand-dug wells (4–8 m deep) were collected and analyzed for pH, turbidity, and dissolved organic carbon before chlorination. Then another set of water samples from the same 13 wells was chlorinated using the methods commonly practiced in this area, consistent with WHO recommended doses. The chlorination degradation products, THMs, trichloromethane, bromodichloromethane (CHCl2 Br), dibromochloromethane (CHClBr2 ), and tribromomethane, were determined at three different times of 60, 180, and 300 min after chlorination, while residual chlorine was determined immediately after chlorination and at 60 and 1, 440 min after chlorination. THMs were determined using gas chromatography (GC), while residual chlorine was determined colorimetrically. Then cancer risk estimation from ingestion, inhalation, and dermal routes was carried out. All water samples from the 13 wells showed elevated amounts of THMs, which also increased with increasing contact time. For instance, the concentrations of THMs at 60 min after chlorination ranged from 24.3 ± 2.0 to 61.3 ± 1.0 μg/L, while at 180 and 300 min, ranged between 85.6 ± 4.3–146.9 ± 2.5 μg/L and 188.1 ± 7.1–250.1 ± 7.1 μg/L, respectively. It was observed that tribromomethane was not detected at all in all samples, while CHCl2 Br and CHClBr2 were only detected at 180 and 300 min post chlorination. The lifetime cancer risk estimation results showed negligible risk at 60 min post chlorination. However, at 180 and 300 min post chlorination, the results were far above negligible, but within the regulatory US EPA limits. The overall risk, however, could not be ignored, given a multiplicity of exposure to various other contaminants, raising concerns over additivity and synergistic interactive effects, particularly for non-cancer hazard indices. HIGHLIGHTS: There was a high prevalence of trihalomethanes (THMs) in chlorinated water from shallow hand-dug wells in peri-urban settings of Mufulira, Zambia. THMs concentrations increased with time post chlorination thereby increasing possible health risks. Despite high levels of THMs, lifetime cancer risks were found to be within acceptable limits for the community of Mufulira, Zambia. Graphical Abstract